Among wolves [videorecording (DVD)] - Lee, Justin (Director); Adkins, Trace; Fahey, Jeff; Pratt, Victoria, 1970-; Locke, Spencer, 1991-; Russo, James; Smith, Forrie J.; Berenger, Tom, 1949- (Shout! Factory, 2023)
Two religious ladies, who witnessed brutal murders, are forced to go on the run and find themselves under the wing of two morally gray outlaws who ferry them to safety.